Proceedings of the 16th International Symposium on Power Semiconductor Devices &Amp;amp; IC's 2004
DOI: 10.1109/wct.2004.239815
|View full text |Cite
|
Sign up to set email alerts
|

MOSFET-mode ultra-thin wafer PTIGBTs for soft switching application $theory and experiments

Abstract: We have proposed and analyzed MOSFET-mode operation of ultra-thin wafer PTlGBTs in ISPSD02[1]. The present paper, for the first time, presents analytical theory of MOSFET-mode operation, and shows that the SOA is determined by a mechanism similar to the second breakdown of npn bipolar transistors.demonstrates, for the first time, that the MOSFETmode IGBTs are strongly effective for sofl switching application. The developed MOSFET-mode 9OOV 60A thin wafer Trench Gate PTlGBTs have reduced turn-off loss by 55% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…TCAD simulations show that the relocation of the electric-field peak from the chip front side towards the field-stop layer [6]- [7], and the occurrence of a lowfield/quasi-plasma region beneath the MOS cells [8], are necessary for the filament formation. The short-circuit current/gate-emitter voltage at which these two conditions are fulfilled increases with the collector-emitter voltage (Fig.…”
Section: Tcad Simulation Of the Filamentation Bordermentioning
confidence: 99%
“…TCAD simulations show that the relocation of the electric-field peak from the chip front side towards the field-stop layer [6]- [7], and the occurrence of a lowfield/quasi-plasma region beneath the MOS cells [8], are necessary for the filament formation. The short-circuit current/gate-emitter voltage at which these two conditions are fulfilled increases with the collector-emitter voltage (Fig.…”
Section: Tcad Simulation Of the Filamentation Bordermentioning
confidence: 99%
“…If it is too low, the negative space charge caused by the electrons flowing from the cathode to the anode may cause a strong increase of the electric-field strength near the n − -n junction formed by the n − -base region and the n-FS region. Extensive investigations [29][30][31][32][33] have shown that the uniform current-density distribution under such conditions can be destabilised by the appearance of single or multiple current filaments. Furthermore, recent device simulations [33] have shown that destabilisation of the uniform current-density distribution may be triggered even in the absence of impact ionisation in the anodeside high-field region.…”
Section: Increased Short-circuit Robustness By the Concept Of Injectimentioning
confidence: 99%
“…To further investigate the ruggedness of the 1200V IGBT, unclamped inductive tests were carried out to evaluate the device avalanche capability at high temperatures. The dynamic tests forces the IGBTs into self-clamp mode during turn-off and measures the device ruggedness and such conditions [4]. Figure (7) shows the voltage and current waveforms obtained from avalanche testing at 200°C.…”
Section: Rbsoa and Avalanche Capability Up To 200°cmentioning
confidence: 99%